The expression of (5a³ⁿ)³ in positive exponents using the law of indices is 125 a⁹ⁿ
The expression has exponents. Therefore, let's express it with a positive exponent.
Therefore,
(5a³ⁿ)³
Hence, let distribute the outside exponents(law of indices),
(5a³ⁿ)³ = 5³ × a³ⁿ ˣ ³
Therefore,
5³ × a³ⁿ ˣ ³
5 × 5 × 5 = 5³ = 125
a³ⁿ ˣ ³ = a⁹ⁿ
Hence,
(5a³ⁿ)³ = 125 a⁹ⁿ
learn more on exponents here: brainly.com/question/2289511
#SPJ2
Answer:
It would be 125a^9n
Answer:
Step-by-step explanation:
x > -9/5 or x < 17/5.
is your answer btw are you always that beutiful?
:)
Using the concepts of complementary angles and bisecting angles, we find that Angle KLM measures 60 degrees and Angle MLN measures 30 degrees.
In this problem, we're dealing with complementary angles and bisecting an angle. Complementary angles are two angles whose measures sum to 90 degrees. When an angle is bisected, it is split into two equal smaller angles.
Firstly, as angle KLM and angle MLN are complementary, the sum of their measures equals 90 degrees, so Angle KLM + Angle MLN = 90 degrees.
Secondly, as angle LM is bisecting angle KLM, this means that angle KLM is split into two equal parts. Let's assume each of those parts is x, that means Angle KLM = 2x.
Given that angle KLM and angle MLN are complementary, we can substitute angle KLM = 2x into the equation, leading us to 2x + Angle MLN = 90 degrees. Since angle MLN is also x because it's a part of bisected angle KLM, we can substitute in Angel MLN = x into this equation, ending up with 2x + x = 90 degrees or 3x = 90 degrees. Solving for x, we find that x = 90 / 3 = 30 degrees.
Therefore, the measure of Angle KLM (2x) is 60 degrees and the measure of Angle MLN (x) is 30 degrees.
#SPJ2
Answer:
Step-by-step explanation:
The distributive says that:
To find the product of :
then;
Using distributive property we have;
Combine like terms;
Therefore, the product of is,
The product of (2x - 1)(x + 4) is .
Here, we have,
To find the product (2x - 1)(x + 4), we need to use the distributive property to multiply each term in the first expression (2x - 1) by each term in the second expression (x + 4).
Using the FOIL method (First, Outer, Inner, Last), we multiply the corresponding terms:
(First terms)
(2x) * (4) = 8x (Outer terms)
(-1) * (x) = -x (Inner terms)
(-1) * (4) = -4 (Last terms)
Now, we combine the products:
Simplifying further:
So, the product of (2x - 1)(x + 4) is .
To learn more on multiplication click:
#SPJ6
complete question:
What is the product? (2x – 1)(x + 4)=?